NEW UPPER ORDOVICIAN STROMATOPOROIDEA FROM TAIMYR - Khromykh V.G. (My University, 2001)
For the first time, a large variety of Stromatoporoidea is recorded from the Ordovician of the southern facies zone of the Taimyr Peninsula. Seven new species and two new genera are described. The majority of Ordovician Stromatoporoidea have secondary tissue surrounding the vertical skeletal elements.
Keywords: Ordovician; Stromatoporoidea; Taimyr Peninsula; Paleozoic::Ordovician; Палеозой::Ордовикская